Evaluation of the PASCO Strep Plus Broth Microdilution Antimicrobial Susceptibility Panels for Testing Streptococcus pneumoniae and Other Streptococcal Species - Mohammed, M. Jasmine (American Society for Microbiology, 2000)
Antimicrobial resistance continues to increase worldwide among isolates of Streptococcus pneumoniae and other species of streptococci. Increasing rates of penicillin resistance, particularly in viridans group streptococci, and resistance to multiple classes of antimicrobial agents, including β-lactams, macrolides, and fluoroquinolones, in pneumococci have increased the importance of having accurate antimicrobial susceptibility testing results for guiding therapy. One commercial method of assessing resistance in streptococci is the PASCO Strep Plus panel. This broth microdilution-based method has recently been expanded to include a variety of newer antimicrobial agents. Therefore, we compared the results of the new PASCO Strep Plus panels for 26 antimicrobial agents against the results generated using the National Committee for Clinical Laboratory Standards (NCCLS) broth microdilution reference method for 75 pneumococci and 68 other streptococcal isolates. Only 4 (0.2%) very major errors (all with pneumococci and each with a different antimicrobial agent) were observed. There were 5 (0.3%) major errors observed with pneumococci (each with a different antimicrobial agent), but only 1 major error with nonpneumococcal streptococci. All of the very major and major errors resolved on retesting. Of the 65 (3.9%) and 17 (1.6%) minor errors observed with pneumococci and other streptococci, respectively, all were within 1 dilution of the broth microdilution reference MIC result. Thus, the PASCO Strep Plus panel has comparable accuracy to the NCCLS broth microdilution reference method.